Examining the Viability of FPGA Supercomputing. (10th January 2007) - Craven, Stephen; Athanas, Peter
Abstract : For certain applications, custom computational hardware created using field programmable gate arrays (FPGAs) can produce significant performance improvements over processors, leading some in academia and industry to call for the inclusion of FPGAs in supercomputing clusters. This paper presents a comparative analysis of FPGAs and traditional processors, focusing on floating-point performance and procurement costs, revealing economic hurdles in the adoption of FPGAs for general high-performance computing (HPC).